Sex Differences in the Overlap Between Bullying Perpetration and Victimization: A Developmental Perspective - Kim, Jihoon (Journal of developmental and life-course criminology, 2023)
Despite considerable empirical attention to the nature of bullying, the overlap between bullying perpetration and victimization remains relatively overlooked. Moreover, even less is known about how these relationships vary across sex from a developmental perspective. This study examines sex differences in the overlap between bullying victimization and perpetration of South Korean youth. Cross-lagged dynamic panel modeling was used to estimate individual differences and within-individual changes in bullying victimization and perpetration and to assess how these overlaps differ by sex. An increase in bullying victimization was related to increased bullying perpetration for both boys and girls, while there were sex differences in the influences of bullying perpetration on bullying victimization. Findings suggest that bullying prevention and intervention programs should consider sex differences.